Evaluasi Kinerja Finansial PT. Semen Indonesia (Persero) Tbk: Analisis Rasio Profitabilitas pada Periode 2016-2020 dan Implikasinya bagi Pemangku Kepentingan - Re Dirgantara; Febrian Hercahyo (Asosiasi Riset Ilmu Manajemen dan Bisnis Indonesia, 2024)
This research aims to evaluate the financial performance of PT. Semen Indonesia (Persero) Tbk with a focus on profitability ratio analysis during the 2016-2020 period. Through collecting financial data and applying the ratio analysis method, this research provides a comprehensive picture of the company's financial health and identifies the implications of the analysis results for stakeholders. The results of this research can provide valuable insight for company management, investors, financial analysts and related parties in making strategic decisions.